2014
DOI: 10.1111/obr.12227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of childhood obesity prevention programmes on blood lipids: a systematic review and meta‐analysis

Abstract: Summary Aim We aimed to assess the effects of childhood obesity prevention programs on blood lipids in high-income countries. Methods We searched MEDLINE®, Embase, PsychInfo, CINAHL®, clinicaltrials.gov, and the Cochrane Library up to April 22, 2013 for relevant randomized controlled trials, quasi-experimental studies, and natural experiments published in English. Studies were included if they implemented diet and/or physical activity intervention(s) with ≥ one year follow up (or ≥ six months for school-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 32 publications
3
30
0
1
Order By: Relevance
“…The significant improvement of the blood lipid profile has also been reported in previous intervention studies [8,9,31,32]. Two recent systematic review and meta-analysis showed that fewer than half of the included studies reported the improvements of HDL and FPG [9,32]. Likewise, in the present study, the nutrition education and physical activity intervention posed a significant improvement in HDL and a decrease in FPG among schoolchildren with obesity.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The significant improvement of the blood lipid profile has also been reported in previous intervention studies [8,9,31,32]. Two recent systematic review and meta-analysis showed that fewer than half of the included studies reported the improvements of HDL and FPG [9,32]. Likewise, in the present study, the nutrition education and physical activity intervention posed a significant improvement in HDL and a decrease in FPG among schoolchildren with obesity.…”
Section: Discussionsupporting
confidence: 86%
“…Despite numerous studies having explored the effectiveness of school-based childhood obesity interventions, results on the cardiovascular risk profile have been inconsistent [8,9]. A meta-analysis showed differential intervention effects on anthropometric and blood lipids outcomes, with more than half of 17 studies showing no significant effect on either, while three of interventions demonstrated beneficial changes on both [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence on the effectiveness of interventions implemented in other settings is generally insufficient. Other analyses and findings from this systematic review on other outcomes such as on blood pressure and blood lipids can be found and were reported recently elsewhere .…”
Section: Discussionmentioning
confidence: 85%
“…9, 10, 11 The stabilization of child obesity rates is positive for public health, but there is strong evidence that child obesity remains unequally distributed across subgroup populations, 12, 13 and that in some countries obesity trends among children from socially disadvantaged backgrounds and certain ethnicities are not stabilizing. 14, 15, 16 The evidence suggests that some child obesity interventions are effective; 17, 18, 19, 20 however, changing obesogenic factors is not a linear process, rather, change is time dependent and complex, and involves interactions between biology, environment and behavior. These interactions may differ across population groups, which may explain why the current interventions are not having the desired impacts in socially disadvantaged communities.…”
Section: Introductionmentioning
confidence: 99%